PENGARUH PEMBERIAN DEKOK DAUN SIRSAK, KUNYIT PUTIH, DAN DAUN KERSEN SERTA KOMBINASINYA DALAM AIR MINUM TERHADAP PERFORMANS DAN KOLESTEROL DARAH AYAM PETELUR JANTAN YANG DIINFEKSI BAKTERI ESCHERICHIA COLI - Erni Ferawati Kadja; J F BaleTherik; Maxs U. E. Sanam (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2018)
The purpose of this study was to determine the effect of soursop leaf (Annona muricata), saffron white (Curcuma mangga Val.) and cherry leaves (Muntingia calabura L.) and theirs combinations in drinking water on performances and blood cholesterol of laying roosters that infected by Escherichia coli. This study was designed using completely randomized design (CRD) with 11 treatments and 3 replications and each treatment using the 4 roosters. That obtained 33 experimental units. The treatments were the drinking water contain decoction of soursop leaves (DS), saffron white (KP) and cherry leaves (DK), and combinations were as follows: R0: without decoction of herbs (control), R1: 6% of DS decoction, R2: 6% of KP decoction, R3: 6 % of DK decoction, R4: 2% of DS decoction + 4% of KP decoction, R5: 2% of DS decoction + 4% of DK decoction, R6: 2% of KP decoction + 4% of DS decoction, R7: 2% of KP decoction + 4% of DK decoction, R8: 2% of DK decoction + 4% of DS decoction, R9: 2% of DK decoction + 4% of KP decoction, R10: 2% of DS decoction + 2% of KP decoction + 2% of DK decoction. Parameters of performance were: feed consumption, water intake, body weight gain, feed conversion. The result showed that the treatment had no effect on the performances (feed consumption, water consumption, body weight gain, feed conversion).